2009
DOI: 10.1111/j.1365-2656.2009.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐level diet variation in four species of Brazilian frogs

Abstract: Summary 1.Many natural populations exploiting a wide range of resources are actually composed of relatively specialized individuals. 2. This interindividual variation is thought to be a consequence of the invasion of 'empty' niches in depauperate communities, generally in temperate regions. If individual niches are constrained by functional trade-offs, the expansion of the population niche is only achieved by an increase in interindividual variation, consistent with the 'niche variation hypothesis'. 3. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 75 publications
(192 reference statements)
10
119
1
1
Order By: Relevance
“…However, for a long time, at least in the case of amphibians, the individual contribution to the population trophic niche variation has remained largely unexplored. Recent reviews by Araújo et al (2009Araújo et al ( , 2011 and Bolnick et al (2003Bolnick et al ( , 2007 demonstrated that several temperate and tropical amphibian populations are indeed composed of a significant number of specialized individuals. This intrapopulation differentiation may become more intense when different prey types concentrate in different spatial patches where predators possessing different morphologies are attracted, or where behavioural or physiological adaptations are selected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for a long time, at least in the case of amphibians, the individual contribution to the population trophic niche variation has remained largely unexplored. Recent reviews by Araújo et al (2009Araújo et al ( , 2011 and Bolnick et al (2003Bolnick et al ( , 2007 demonstrated that several temperate and tropical amphibian populations are indeed composed of a significant number of specialized individuals. This intrapopulation differentiation may become more intense when different prey types concentrate in different spatial patches where predators possessing different morphologies are attracted, or where behavioural or physiological adaptations are selected.…”
Section: Discussionmentioning
confidence: 99%
“…In amphibians, ontogenetic, morphological, and seasonal variations in individual trophic specialization have been described only recently and in a small number of species (e.g., Collins et al 1993;Maret and Collins 1997;Maerz et al 2006;Araújo et al 2009;da Rosa et al 2011;Schriever and Williams 2013). However, understanding the contribution of individual trophic specialization may allow for better understanding of population realized trophic niche and its contribution to the ecological food web, especially in those species that connect freshwater and terrestrial ecosystems (i.e., Regester et al 2006) or in populations that play a relevant role in energy storage and turnover in the litter of forest ecosystems (reviewed in Davic and Welsh 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such a positive relationship between niche width and the level of individual heterogeneity is supported in taxa as diverse as gasteropods, fish, amphibians, or reptiles ). This relationship could, however, also be extended to the inter-specific level (Araújo et al , 2009; the level of individual heterogeneity in terms of niche width is expected to be larger in generalist species than in specialist species. Indeed, specialist species may be constrained by cognitive, physiological or morphological adaptations imposing a limit to inter-individual variation (Bolnick et al 2003).…”
mentioning
confidence: 99%
“…Since frogs grow substantially after metamorphosis to reach adult size, they could be expected to experience considerable diet shifts during the terrestrial phase of their life cycle, but this was not found to be the case here. Stomach content analysis supported the isotope findings by showing that both juvenile and adult E. nattereri tend to specialize on ants and termites (Araujo et al 2009). …”
Section: Discussionsupporting
confidence: 53%